Investigating Student Engagement and Making Science Real during a Pandemic: Bioskills at Home, a Case Study - Sarah Rayment; Karin Garrie; Ishwinder Kaur; Gareth McVicker; Emma Storey; Jody Winter; Luigi A. De Girolamo; Callum Rimmer; David Negus; Carl Nelson; Jonathan Thomas; Michael Loughlin; et al. (MDPI AG, 2022)
Development of key practical skills is fundamental to bioscience courses in higher education. With limitations on access to laboratory time due to the COVID-19 pandemic, a "Bioskills at home" kit was developed to create opportunities for first year undergraduate students to develop these skills using online support resources to guide their activities and build communities of learning. Equipment and activities in this kit enabled students to practice key skills such as pipetting, data handling, experimental design and microscopy, as well as build an online peer learning community through the use of discussion boards and microscopy competitions that encouraged students to explore their local environment. Students who engaged with these activities reported increased confidence in key practical skills. Practical assessment of skills showed that that there was no reduction in the proportion of students who succeeded in achieving the pipetting learning objective compared to previous years, despite a significantly reduced on-campus provision. Although the celebration event to choose the microscopy competition winners was well attended, there was limited use of the discussion boards by students to build a community of learning during the term. Refinement of this initiative will focus on providing greater scaffolding to encourage greater engagement with activities and enhance community building.